Pengaruh Burnout dan Job Insecurity terhadap Turnover Intention - Refi Pramisti; Allya Roosallyn Assyofa; Indra Fajar Alamsyah (Bandung Conference Series: Business and Management, 2024)
Abstract. This study aims to examine and analyze the effect of burnout and job insecurity on turnover intention at the shop keeper clothing brand Jalan Sultan Agung, Bandung. The data used in this study are primary and secondary data. The population in this research is the shop keeper clothing brand Jalan Sultan Agung Bandung. The sampling technique in this study used non-random sampling. The analytical tool used is Multiple Linear Regression. The test results show that burnout has a positive and significant effect on turnover intention, job insecurity has a positive and significant effect on turnover intention. Burnout and Job insecurity simultaneously influence turnover intention.